Toxoplasma gondii Syntaxin 6 is required for vesicular transport between endosomal-like compartments and the Golgi complex. - Jackson, A; Clucas, C; Mamczur, N; Ferguson, D; Meissner, M (2013)
Apicomplexans are obligate intracellular parasites that invade the host cell in an active process that relies on unique secretory organelles (micronemes, rhoptries and dense granules) localized at the apical tip of these highly polarized eukaryotes. In order for the contents of these specialized organelles to reach their final destination, these proteins are sorted post-Golgi and it has been speculated that they pass through endosomal-like compartments (ELCs), where they undergo maturation. Here, we characterize a Toxoplasma gondii homologue of Syntaxin 6 (TgStx6), a well-established marker for the early endosomes and trans Golgi network (TGN) in diverse eukaryotes. Indeed, TgStx6 appears to have a role in the retrograde transport between ELCs, the TGN and the Golgi, because overexpression of TgStx6 results in the development of abnormally shaped parasites with expanded ELCs, a fragmented Golgi and a defect in inner membrane complex maturation. Interestingly, other organelles such as the micronemes, rhoptries and the apicoplast are not affected, establishing the TGN as a major sorting compartment where several transport pathways intersect. It therefore appears that Toxoplasma has retained a plant-like secretory pathway.